Analysis of the Use of Indonesian Spelling in the Opinions of the Singgalang Newspaper - Nur Safina; Yulia Sri Hartati; Indriani Nisja (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
This study analyzes the Use of Indonesian Spelling in the Language of Singgalang Newspaper Opinions. The formulation of the research problem is how is the use of Indonesian spelling in writing letters, writing words, and writing punctuation in the language of Singgalang newspaper opinions? This type of research is qualitative research with a descriptive method. This study uses data validation techniques in the form of theory triangulation techniques. The data in this study are in the form of quotations from the use of Indonesian spelling and the data source in this study is the opinion of the Singgalang newspaper. This study took the data source based on purposive sampling, the data and data sources obtained will be described and analyzed to obtain Indonesian spelling in the language of Singgalang newspaper opinions. This research was collected in two stages, namely documentation and reading and writing. The results of the study in the language of Singgalang opinions found the use of letters, namely in capital letters, the use of words, namely in affixes, prepositions, particles, abbreviations, acronyms, numbers, and the use of punctuation points, commas, colons, hyphens, dashes, question marks, double quotation marks, brackets and slashes. The use of spelling in the opinions of the Singgalang newspaper was found to be a total of 107 representative data and 232 data from the five political opinions that had been analyzed previously.